The Effect of Work Environment, Work Ethics, Work Culture, and Work Motivation on Performance of Environmental Services in Labuhanbatu Regency - Nur Aini; Ade Parlaungan Nasution; Nurintan Asyiah Siregar (Quantitative Economics and Management Studies, 2022)
Source power man is factor mover main from whole activity company . Type study this character quantitative , which becomes the place study this is Environmental Service Labuhanbatu district. In study this is what becomes population is employee Environmental Service Labuhanbatu as many as 30 people. Data collection is carried out with a spread questionnaire using google form and measured with a scale likert. Data analysis techniques in research this use PLS (partial least square) analysis which is analysis equality -based Structural Equation Modeling (SEM) variant with use softwear SmartPLS 3. Research results this show that environment work , ethics work , culture work and motivation work take effect significant to performance Environmental Service Labuhantu district.